Neuro-Muscular Rehabilitation Through Basti and Mamsa Pinda Sweda in Hirayama Disease (AYUSHDHARA, 2025)
Hirayama disease is characterised by juvenile onset of unilateral muscular atrophy of distal upper extremity. The disability originates with impaired functioning of anterior horn cells of the cervical cord. Studies consistently note a loss of the cervical lordosis and compression of the cervical cord by the dural sac in forward flexion. Here is a case report of a 24-year old male with Hirayama disease who had been treated as inpatient. The case was considered as a Vatavyadhi and the treatment protocol applied accordingly with incorporation of treatment of Asthikshaya, Vishwachi and Bahushosha particularly. The treatment included Abhyanga, Seka, Mamsa Pinda Sweda, Mustadi Yapana Basti and Rasayana Oushadhi. Even though the patient condition was irreversible, he was able to regain the functional status after restarting the treatment. The case highlights the improvement in quality of life of the patient after Ayurvedic management.